2002
DOI: 10.1038/nature731
|View full text |Cite
|
Sign up to set email alerts
|

Control of CpNpG DNA methylation by the KRYPTONITE histone H3 methyltransferase

Abstract: Gene silencing in eukaryotes is associated with the formation of heterochromatin, a complex of proteins and DNA that block transcription. Heterochromatin is characterized by the methylation of cytosine nucleotides of the DNA, the methylation of histone H3 at lysine 9 (H3 Lys 9), and the specific binding of heterochromatin protein 1 (HP1) to methylated H3 Lys 9 (refs 1-7). Although the relationship between these chromatin modifications is generally unknown, in the fungus Neurospora crassa, DNA methylation acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
964
2
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,134 publications
(1,016 citation statements)
references
References 27 publications
38
964
2
12
Order By: Relevance
“…In Neurospora crassa, mutations in Su(var)3-9 H3K9 methyltransferases (dim-5) gene are responsible for a genome wide demethylation of methylated CpGs [72]. The same result was obtained in A. thaliana by mutations of Kryptonite gene, a relative of Su(var)H3-K9 methyltransferase, in this case the CpNpG methylated sequences were largely demethylated while methylation status of CpGs remained unchanged [73]. In mice, mutation of the two Su(var)3-9 homologs has a relatively minor effect on cytosine methylation and causes partial demethylation of major satellite regions of pericentromeric heterochromatin [74].…”
Section: The Connection Between Dna Met Hy-lation and Other Epigenetimentioning
confidence: 66%
“…In Neurospora crassa, mutations in Su(var)3-9 H3K9 methyltransferases (dim-5) gene are responsible for a genome wide demethylation of methylated CpGs [72]. The same result was obtained in A. thaliana by mutations of Kryptonite gene, a relative of Su(var)H3-K9 methyltransferase, in this case the CpNpG methylated sequences were largely demethylated while methylation status of CpGs remained unchanged [73]. In mice, mutation of the two Su(var)3-9 homologs has a relatively minor effect on cytosine methylation and causes partial demethylation of major satellite regions of pericentromeric heterochromatin [74].…”
Section: The Connection Between Dna Met Hy-lation and Other Epigenetimentioning
confidence: 66%
“…has been observed in diverse biological systems (Tamaru and Selker, 2001;Fahrner et al, 2002;Jackson et al, 2002;Fuks et al, 2003;Lehnertz et al, 2003;Tariq et al, 2003;Freitag et al, 2004). Therefore, the different H3-m 3 K9 states in the two species prompted us to investigate DNA methylation states in sperm-derived chromatins.…”
Section: Appearance Of H3-k9 Methylation In Pig But Not In Mouse Spmentioning
confidence: 99%
“…Tamaru and Selker [2001] showed that CpG methylation in Neurospora is dependent on the function of the H3 Lys9 methyltransferase encoded by dim-5. Subsequently, Jackson et al [2002] showed that CpNpG methylation in Arabidopsis thaliana requires function of the Kryptonite (Kyp) H3 Lys9 methyltransferase. Lehnertz et al [2003] showed that mouse ES cells homozygously mutated for Suv39h1 and Suv39h2 (which encode closely-related histone H3 Lys9 methyltransferases specific for centromeric heterochromatin) have reduced DNA methylation of pericentric satellite repeats, but not of other repeat sequences.…”
Section: Pws/as Regionmentioning
confidence: 99%